Nuclear War and Nuclear Peace - Baylis, John. author. aut Link
XIV, 173 p.
Keywords: This study attempts to bring the debate about nuclear weapons and arms control up to date by assessing the reasons for the recent superpower agreement, the decline of the peace movements, the new threats to international stability and the prospects for further detente.